Comparison of acute leukemia image segmentation using HSI and RGB color space - Nor Hazlyna, Harun; Mohd Yusoff, Mashor, Prof. Madya Dr.; Mokhtar, N. R.; Aimi Salihah, A. N.; Hassan, R.; Rafikha Aliana, A. Raof; Osman, M. K. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/